PENANGKAPAN KAPAL NELAYAN VIETNAM DI LAUT NATUNA UTARA TAHUN 2021-2025 BERDASARKAN UNCLOS 1982: The Arrest of Vietnamese Fishing Vessel in North Natuna Sea from 2021 to 2025 based on UNCLOS 1982 - Muhammad Naufal Fadhlurrahman; Yulia Fitriliani (Reformasi Hukum Trisakti, 2026)
Illegal fishing practices by foreign fishing vessels, especially Vietnamese-flagged vessels, still frequently occur in Indonesia's Exclusive Economic Zone (EEZ) in the North Natuna Sea. This phenomenon not only causes economic losses but also constitutes a violation of Indonesia's sovereign rights as regulated in the 1982 United Nations Convention on the Law of the Sea (UNCLOS). The problem aims to how law enforcement against foreign vessels conducting illegal fishing in Indonesia's EEZ and analyze the resolution of illegal fishing cases carried out by Vietnamese fishing vessels based on the provisions of UNCLOS 1982. The research method used is normative legal research with a statutory and conceptual approach, through a literature study of primary and secondary legal materials. The results and conclusion of the study indicate that Indonesia has a strong legal basis to conduct supervision, inspection, arrest, and legal action against foreign vessels in the EEZ based on Article 56 and Article 73 of UNCLOS 1982 and national laws and regulations. Illegal fishing cases are resolved through national legal mechanisms, while still respecting sanctions against foreign crews and supported by diplomatic efforts and bilateral cooperation. This law enforcement reflects Indonesia's efforts to protect its sovereign rights while respecting principles of international maritime law.